Assessment of mutagenic and antimutagenic effects of Punica granatum in mice - Marize Campos Valadares; Enir Raquel Tavares Pereira; Polyana Lopes Benfica; José Realino Paula (Universidade de São Paulo, 2010)
In the present study, the ability of Punica granatum ethanolic leaf extract (PGL) and Punica granatum ethanolic fruit extract (PGF) to induce mutagenicity or to modulate the genotoxic effects induced by the alkylating agent cyclophosphamide (CP) was evaluated. Swiss male mice were treated by gavage for 10 days with PGL or PGF (12.5, 25, 50, and 75 mg/kg/day) prior to exposure to CP (i.p. 200 mg/kg), 24 h after the end of the treatment. Initial observations revealed that normal mice treated with both extracts (12.5, 25, 50, and 75 mg/kg/day) showed a similar micronucleated polychromatic erythrocyte (MNPCE) frequency to that of the control group. Investigation of the protective effect of PGL and PGF based on data analysis revealed that, irrespective of dose or extract, oral administration of PGL or PGF for 10 days prior to exposure had reduced, in a dose-dependent manner, the frequency of MNPCE induced by CP in all groups studied. Higher reductions were observed at PGF doses of 50 and 75 mg/kg. Taken together, these results demonstrate that mice treated with P. granatum showed an absence of mutagenic effects and dose-dependent protective effects against CP-induced oxidative DNA damage.